Perilaku Harian Tarsius Dalam Kandang di Patunuang, Taman Nasional Bantimurung Bulusaraung - Maryatul Qiptiyah; Bayu Wisnu Broto; Titiek Setyawati (Foresty Faculty of Hasanuddin University, 2012)
Tarsius is one of the protected and endegered species. This study aims to examine the behavior of Tarsius fuscus in captivity in Patunuang, Batimurung Bulusaraung National Park, South Sulawesi Province. The observations were made from March until October of 2011, with 6 periods of observation and each the observations made during of three days from 15:00 pm until 8:00 am. The observations were not done during the day because Tarsius don't present any activity during daylight. The observed behaviors were ingestive, allelomimetic, agonistic, shelter-seeking, grooming, eliminative, playing, and resting behaviors. Observations indicated that the behavior of Tarsius which has the highest proportion was playing, followed by allelomimetic and rest behavior.